The Love Argument for the Trinity: A Reformulation - Sijuwade, Joshua (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
The central focus of this article is to provide a new “Love Argument” for the necessary truth of the Latin' model' of the doctrine of the Trinity—termed “Latin Trinitarianism”—from an a priori standpoint. This new argument, called the Agápēic Argument, will be formulated in light of the metaphysical notions of a “trope,” introduced by D. C. Williams, and “multiple location,” posited by Antony Eagle, and the ethical concept of agápē, proposed by Alexander Pruss. Doing this will provide a specific argument that provides strong grounds for affirming the necessary truth of the Trinity, without, however, being subject to the primary objections that have been often raised against the existing versions of the argument.